Application of 3D-volumetric analysis and hyperspectral imaging systems for investigation of heterosis and cytoplasmic effects in pepper - Chang, Sungyul; Lee, Unseok; Kim, Jin-Baek; Jo, Yeong Deuk (Elsevier BV, 2022)
Compared with the substantial amount of genomics data generated in recent years, phenotypic data availability for crops is largely restricted in spectrum and quantity. High-throughput phenotyping (HTP) platforms have been developed to overcome this limitation, not only by enhancing the speed and accuracy of phenotyping but also by expanding the range of evaluable traits through integration of various imaging systems. Three-dimensional (3D) imaging enables non-destructive estimation of plant volume and structure. Hyperspectral imaging (HSI) generates reflectance data for a broad range of wavelengths that are associated with diverse physiological traits. We performed a pilot study to apply 3D and HSI for investigation of heterosis and cytoplasmic effects that have been evaluated previously based on manually analyzable traits. The plant volumes estimated from 3D images by a customized pipeline quantitatively showed heterosis in three cross combinations between genetically distant pepper (Capsicum annuum) accessions. The normalized difference vegetation index (NDVI) derived from HSI reflectance data also showed differences between parental and F-1 lines. The cytoplasmic effects investigated by comparison of F-1 lines derived from reciprocal crosses was subtle and thus was not detected in plant volume or NDVI values. However, the difference between F-1 lines was detected in a subset of cross combinations at a specific developmental stage based on reflectance for wavelength ranges selected as the most relevant. The results showed the potential utility of HSI data recorded throughout the plant life-span for analysis of cytoplasmic effects. The present study demonstrated the applicability of a HTP platform integrated with 3D and HSI systems for evaluation of combining ability in crops.